The effect of hydro cooling time, storage temperature and storage duration on Saba banana - Jagathiswarri SupramaniamJagathiswarri Supramaniam; Salumiah Mijan; Januarius Gobilik; Jupikely James Silip (Faculty of Science and Natural Resources, 2021)
This study was conducted in Postharvest Lab of Faculty Sustainable Agriculture. The objective of this study was to determine the effect of hydro cooling time, storage temperature and storage duration on Saba banana. The hypothesis that has been tested in this experiment was there a significant difference in the effect of hydro cooling time (CT), storage temperature (ST) and storage duration (SD) on Saba banana. The experimental design that used for this study was Completely Randomised Design (CRD) with a factorial arrangement of treatments (3 CoolingTime x 3 Storage Temperature x 4 Storage Duration), with three replications and two fruits per treatment per replication. The results were analysed using SAS Version 9.1. Analysis of variance (ANOVA) was used to get the variance among the treatments, storage temperatures and storage duration. LSD was performed to determine difference on the mean values. The results indicate that the hydro cooling time has significantly affected all the observed parameters. irrespective of cooling time, precooled fruits showed lower weight loss and low degradation on the visual appearances. However, none of cooling time in this study could be recommended as indicated lead to disadvantage. Therefore, this result suggests for future study to test lower or shorter cooling time such as 1/8 and ¼ cooling time.